Eksistensi Komunitas Musik Yayasan Halim Dalam Mengembangkan Musik Tradisional Tionghoa di Jalan Gajah Mada Kecamatan Pontianak - Pensius, Angga Dion; Djau, Nurmila Sari; Grandena, Egi Putri (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2024)
The background of this research is the existence of Halim Foundation Chinese traditional music which still exists today. The goal achieved is to find out the development of Halim Foundation's traditional music from time to time, by documenting in the form of writing supported by photographs related to Halim Foundation's traditional Chinese music, so that Halim Foundation's traditional Chinese music can be known by the wider community. The method used in this research is descriptive method and qualitative research research form. Data collection techniques in this study are interviews, observations and documentation studies. Data validity techniques use triangulation techniques and extended observation. Data analysis used several stages, namely reduction, data presentation. The results of this study, the Halim Foundation's traditional Chinese music community has undergone an impressive journey in preserving and promoting traditional Chinese music in the Gajah Mada street area, this community has achieved impressive achievements. the way the Halim Foundation community develops traditional Chinese music is to hold regular rehearsals and often perform in big events. Then regenerate by inviting young people who want to learn Chinese music. In addition, widespread support from the community proves that the efforts of the Halim Foundation community are well appreciated and recognized. the involvement of many people shows that traditional Chinese music still has a special place in the hearts and lives of local communities.